Antiretroviral Preexposure Prophylaxis for Heterosexual HIV Transmission in Botswana - Thigpen, Michael C; Kebaabetswe, Poloko M; Paxton, Lynn A; Smith, Dawn K; Rose, Charles E; Segolodi, Tebogo M; Henderson, Faith L; Pathak, Sonal R; Soud, Fatma A; Chillag, Kata L; Mutanhaurwa, Rodreck; Chirwa, Lovemore Ian; et al. (The New England journal of medicine, 2012)
In this study, 1219 HIV-uninfected, heterosexual adults in Botswana were randomly assigned to tenofovir–emtricitabine (TDF–FTC) or placebo. The TDF–FTC group had a lower incidence of HIV infection but increased rates of side effects, including a significant loss of bone density. Biomedical strategies to prevent sexual transmission of human immunodeficiency virus (HIV) remain limited. 1 In animal models, preexposure prophylaxis with tenofovir disoproxil fumarate (TDF) or with the combination of TDF and emtricitabine (TDF–FTC) can prevent infections with HIV or hybrid simian–human immunodeficiency virus after vaginal or rectal challenge. 2 , 3 In humans, daily preexposure prophylaxis with TDF–FTC has been shown to reduce transmission of HIV by 44% among men who have sex with men 4 ; however, the findings from studies in heterosexual populations have been mixed. 5 – 8 Botswana has the world's second highest prevalence of HIV infection, estimated in 2008 to be . . .